Cerebral cavernomas in infancy and atypical development of communication and language - Álvarez, Carlos G.; Torres Morales, Felipe; Culcay, Laura C.; Bascuñán Vidal, Javiera Amapola (Revista de Investigación en Logopedia, 2021)
Cerebral cavernomas are vascular malformations of the central nervous system and are uncommon in the pediatric population. These malformations may appear as single or multiple lesions. Symptoms of cerebral cavernomas are mainly associated with the topography of the lesion. This article reports the communicative and linguistic abilities of a child aged 3 years 10 months who is diagnosed with multiple cerebral cavernomatosis and discusses the potential relationship between demonstrated abilities and the child’s neurological background. The inquiry was performed through the application of the following three procedures: 1. review of clinical records in medical files, 2. creation and analysis of naturally-occurring communication and language samples, 3. application and analysis of the MacArthur Communicative Development Inventories. The qualitative analysis of the compiled records allows for the suggestion of an association between observed atypical communication and language abilities and the diagnosis of multiple cerebral cavernomatosis, in particular due to the topographical location of the lesions. To the best knowledge of the authors, this article represents the first description of atypical communication and language abilities associated with the diagnosis of multiple cerebral cavernomatosis in the pediatric age group.